Hukum Kausalitas Dalam Perspektif Pengembangan Ilmu Pengetahuan Modern - Zikri, Abdalul; Jailuddin, Syuaib; M, Marilang; Siola, M. Nasir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Causality is one of the most important topics in the history of philosophy, this is because the principle of causality is one of the main issues in the tradition of Islamic philosophy where the principle of causality is a fundamental issue in philosophy. In the Middle Ages, Muslim philosophers were busy with productive debates about causality that were seen solely from Islamic philosophy and Islamic theology, thus giving rise to debates among philosophers where each philosopher had his own opinion. In fact, it can be said that awareness of the world and representation in the world always depend on causal relationships. Finding all the relationships between cause and effect also provides insight into the causal structure of nature and forms the ability to learn to act intelligently in the world. Finding what actually causes the possibility of building causal patterns, and this allows for rational or logical predictions, decisions, and actions in the world. Causality forms a chain that begins in the past, exists in the present, and disappears in the future. The views of philosophers on the principle of causality have evolved from Plato, who emphasized the importance of causes in change, to Aristotle who distinguished four types of causes. The Stoics asserted that every event has a cause, while medieval philosophers distinguished between primary and secondary causes. In modern times, Hume emphasized the need for experience to understand causal relationships, while Kant argued that causality is based on the structure of reason. Mill added that causes are combinations of conditions. Overall, these developments reflect the complexity of views on causality in philosophy.